Polyfactorial approach in rehabilitation of football players’ muscles after sports injuries - Vladymyrov, Oleksandr; Chukhraiev, Nikolay; Shmorgun Аndriy; Zukow, Walery; Мaliuta Vladimir; Chukhraieva, Olena (Journal of Education, Health and Sport, 2022)
The article discusses a multifactorial approach to the restoration of muscle volume and rehabilitation of football players after sports injuries, which includes the implementation of electric myostimulation in a magnetic field in combination with the effect of electromagnetic radiation of the visible or infrared spectrum on muscles and the area of injury. Comparative studies were carried out in two groups of footballers in rehabilitation after ankle injury rehabilitation. The medical rehabilitation of the players of the 1st group was carried out according to the protocol approved in the center: the MIT-FM apparatus, the protocol for the implementation of rehabilitation provides for the implementation of drug treatment and physiotherapeutic procedures based on the combined use of therapy with electromagnetic waves of the red, blue and infrared spectral range with a power of 50 mW in a pulsed magnetic field of intensity 30 mT and a pulse repetition rate of 9.4 Hz. In group 2, the rehabilitation of footballers after injuries of the lower extremities was carried out according to the protocol developed by the authors: sequential connection of the rehabilitation protocol of the first group and combined magneto-photo electric myostimulation of muscles with myotonic impulses, with a pulse repetition rate of 9.4 Hz. The repetition period of the packs of impulses is 8 seconds with the duty cycle of repetition of the packs of impulses 2. The current strength was set individually for each patient - until the appearance of visible muscle contractions. Muscle photostimulation was performed with electromagnetic radiation of red (wavelength 0.63 μm, power 30 mW), blue (wavelength 0.45 μm, power 30 mW) and infrared (wavelength 0.75 μm, power 50 mW) spectral ranges in constant magnetic field (intensity 30 mT). The first electrode is placed on the muscle’s innervation zone. The second electrode provides a combined effect of electrical impulses and optical flux in a constant magnetic field on the abdomen of the muscle according to the labile technique. The time of one procedure was 40 minutes. The number of procedures for a course of treatment is 15. As a result, the analysis of the data obtained (assessment of the quality of life according to the extended table SF-36) revealed a positive dynamics of clinical manifestations in both groups. The main result of the research is the development of a protocol for the rehabilitation of football players after injuries of the lower extremities based on the use of drug treatment, physiotherapy procedures based on the combined use of therapy with electromagnetic waves of the blue and infrared spectrum in a constant magnetic field in combination with muscle electrostimulation, which has a higher level rehabilitation potential versus applicable footballerІ rehabilitation protocols.